THE IMPACT OF SHOPEE PAYLATER USER’S FINANCIAL BEHAVIOR FROM SHARIA PERSPECTIVE - Astutiningsih, Sri Eka; Estiningrum, Sri Dwi; Shadidah, Lutfiah Intan (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
The study examines the impact of loan size and financial risk-taking on the financial behavior of Shopee PayLater users and the alignment of this behavior with Sharia principles. Employing a quantitative method with a descriptive approach and statistical analysis, the primary data was collected through questionnaires distributed to UIN Sayyid Ali Rahmatullah Tulungagung students. The findings highlight a simultaneous positive and significant effect of loan size and financial risk-taking on the financial behavior of Shopee PayLater users, along with a partial positive and significant influence of these factors. Furthermore, the suitability of the financial behavior of Shopee PayLater users from a Sharia perspective is evaluated based on the regulations outlined in the Al-Qur’an and Hadith, particularly regarding shopping, consumption, and debt.